2005
DOI: 10.1167/iovs.05-0543
|View full text |Cite
|
Sign up to set email alerts
|

LBP and CD14 Secreted in Tears by the Lacrimal Glands Modulate the LPS Response of Corneal Epithelial Cells

Abstract: Tear CD14 and LBP complemented the LPS receptor complex expressed by the corneal epithelia to trigger an immune response in the presence of LPS. The complementation of these tear and corneal immune proteins could play an important role in LPS recognition and signaling and, therefore, could modulate ocular innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…TLR3 and TLR5, which are activated by double-stranded RNA and bacterial flagellin, respectively, are also present and functional in human corneal epithelial cells (16,22,38) Although TLR9 has not been described in human corneal epithelial cells, TLR9 activation in the mouse cornea induces keratitis (15) and TLR9 short interfering RNA reduces the severity of Pseudomonas aeruginosa keratitis (12). In contrast, there are conflicting reports of the role of TLR4 in the cornea; two reports indicate it is nonfunctional due to either an intracellular location or the absence of costimulatory molecules (1,35), whereas another report shows that TLR4 is functional (31). The underlying difference for this discrepancy is not clear, but LPS can induce keratitis in murine and rabbit models of epithelial abrasion (15,18,28).…”
Section: Vol 74 2006 Tlr2 and Myd88 In S Aureus Keratitis 5329mentioning
confidence: 99%
“…TLR3 and TLR5, which are activated by double-stranded RNA and bacterial flagellin, respectively, are also present and functional in human corneal epithelial cells (16,22,38) Although TLR9 has not been described in human corneal epithelial cells, TLR9 activation in the mouse cornea induces keratitis (15) and TLR9 short interfering RNA reduces the severity of Pseudomonas aeruginosa keratitis (12). In contrast, there are conflicting reports of the role of TLR4 in the cornea; two reports indicate it is nonfunctional due to either an intracellular location or the absence of costimulatory molecules (1,35), whereas another report shows that TLR4 is functional (31). The underlying difference for this discrepancy is not clear, but LPS can induce keratitis in murine and rabbit models of epithelial abrasion (15,18,28).…”
Section: Vol 74 2006 Tlr2 and Myd88 In S Aureus Keratitis 5329mentioning
confidence: 99%
“…In the present study, we went to determine whether age affects the expression profile of miRNAs in mouse peritoneal macrophages stimulated with or without lipopolysaccharide (LPS), one of the most powerful bacterial virulence factors in terms of proinflammatory properties (Blais et al, 2005). We found that seven miRNAs (miR-101b, miR-223, miR-142-3P, miR-M1-8, miR-146a, miR-26b, and miR-191) were up-regulated in the LPS-stimulated macrophages of young mice but not in aged group.…”
Section: Introductionmentioning
confidence: 99%
“…sTLRs in blood plasma are speculated to be derived from monocytes or macrophages, because sTLR-2 and -4 have been shown to be secreted into the culture supernatant by freshly isolated human monocytes or a mouse macrophage cell line [21,25]. sTLRs are detected in various exocrine glands, such as the parotid gland, lacrimal gland and gland of the uterine cervix using immunohistochemistry or RT-PCR methods [5,14,24]. However, the entire spectrum of sTLRs secretion sites in the animal alimentary tract has never been clarified.…”
mentioning
confidence: 99%